Turning the page on energy poverty? Quasi-experimental evidence on education and energy poverty in Zimbabwe - Makate, Marshall (Elsevier, 2024)
We investigate the long-term causal effects of education on energy poverty among households headed by men and women, leveraging the 1980 Zimbabwe school reform as a quasi-experiment. This reform, which significantly expanded educational opportunities for all children, serves as an ideal setting for assessing the impact of education on energy poverty within a regression discontinuity design, with age at reform determining exposure. Exposure to the reform resulted in a 2.08-year average increase in schooling and a 28.3 percentage point (pp) increase in the probability of completing secondary schooling. The reform's impact was more pronounced for women, increasing their schooling by 2.35 years (compared to 1.68 years for men) and for rural residents, with a 2.53-year increase (compared to 1.00 year for urban residents). A one-year increase in education reduces the risk of energy poverty by an estimated 8.56%, more pronounced among male-head families (5 pp) than among female-headed households (4.6 pp). This increased education enhances labour market outcomes, household economic status, infrastructure quality, and access to information and promotes progressive societal norms. These findings underscore education's crucial role in sustainable and gender-inclusive economic development, highlighting the potential of educational policy in reducing energy poverty and advancing gender equality in low-income countries.